Biophysical analysis of the effect of chemical modification by 4-oxononenal on the structure, stability, and function of binding immunoglobulin protein (BiP). - Dinen D Shah; Surinder M Singh; Monika Dzieciatkowska; Krishna M G Mallela (PLoS ONE)
Binding immunoglobulin protein (BiP) is a molecular chaperone important for the folding of numerous proteins, which include millions of immunoglobulins in human body. It also plays a key role in the unfolded protein response (UPR) in the endoplasmic reticulum. Free radical generation is a common phenomenon that occurs in cells under healthy as well as under stress conditions such as ageing, inflammation, alcohol consumption, and smoking. These free radicals attack the cell membranes and generate highly reactive lipid peroxidation products such as 4-oxononenal (4-ONE). BiP is a key protein that is modified by 4-ONE. In this study, we probed how such chemical modification affects the biophysical properties of BiP. Upon modification, BiP shows significant tertiary structural changes with no changes in its secondary structure. The protein loses its thermodynamic stability, particularly, that of the nucleotide binding domain (NBD) where ATP binds. In terms of function, the modified BiP completely loses its ATPase activity with decreased ATP binding affinity. However, modified BiP retains its immunoglobulin binding function and its chaperone activity of suppressing non-specific protein aggregation. These results indicate that 4-ONE modification can significantly affect the structure-function of key proteins such as BiP involved in cellular pathways, and provide a molecular basis for how chemical modifications can result in the failure of quality control mechanisms inside the cell.